Pendampingan Sistem Pengelolaan Surat Berbasis Web sebagai Solusi Digitalisasi Administrasi Inspektorat Kudus - Mahendra, Indra Wahyu; Widodo, Anteng (Universitas Pahlawan Tuanku Tambusai, 2026)
Correspondence administration is a vital component of the operational activities at the Regional Inspectorate of Kudus, which manages a high volume of incoming and outgoing letters. However, archival management is still conducted manually using logbooks and physical storage, leading to data disorganization, risk of document loss, and delays in information retrieval. This community service activity aims to provide assistance in implementing a web-based correspondence management system as a solution for administrative digitalization. The implementation method includes problem analysis, system development using the Waterfall model with PHP Native and MySQL, user training, and implementation assistance. The developed system features incoming and outgoing mail management, digital disposition, and automated report generation. The results indicate that the system improves administrative efficiency, data security, and accessibility of information, thereby supporting a more structured, paperless, and effective archival management process.